Altered delay discounting in neurodegeneration: insight into the underlying mechanisms and perspectives for clinical applications. (March 2023) - Godefroy, Valérie; Sezer, Idil; Bouzigues, Arabella; Montembeault, Maxime; Koban, Leonie; Plassmann, Hilke; Migliaccio, Raffaella
Abstract: Steeper delay discounting (i.e., the extent to which future rewards are perceived as less valuable than immediate ones) has been proposed as a transdiagnostic process across different health conditions, in particular psychiatric disorders. Impulsive decision-making is a hallmark of different neurodegenerative conditions but little is known about delay discounting in the domain of neurodegenerative conditions. We reviewed studies on delay discounting in patients with Parkinson's disease (PD) and in patients with dementia (Alzheimer's disease / AD or frontotemporal dementia / FTD). We proposed that delay discounting could be an early marker of the neurodegenerative process. We developed the idea that altered delay discounting is associated with overlapping but distinct neurocognitive mechanisms across neurodegenerative diseases: dopaminergic-related disorders of reward processing in PD, memory/projection deficits due to medial temporal atrophy in AD, modified reward processing due to orbitofrontal atrophy in FTD. Neurodegeneration could provide a framework to decipher the neuropsychological mechanisms of value-based decision-making. Further, delay discounting could become a marker of interest in clinical practice, in particular for differential diagnosis. Highlights: Our aim was to integrate the heterogeneous results linking neurodegeneration to abnormal delay discounting. Delay discounting might be altered very early in the course of the neurodegenerative pathology. In each neurodegenerative condition, specific features contribute to alter delay discounting. This could help deciphering the neuropsychological mechanisms of value-based decision-making. Delay discounting could become an interesting marker for early and differential diagnosis of neurodegenerative diseases.